Borrowing constraints, effective flexibility in labor supply, and portfolio selection - Lee, Ho Seok; Shim, Gyoocheol; Shin, Yong Hyun (Mathematics and Financial Economics, 2019)
We study optimal job switching and consumption/investment policies of an economic agent under the borrowing constraints against future labor income in a continuous and infinite time horizon. The agent’s preference is given by the Cobb–Douglas utility function whose arguments are consumption and leisure, and the jobs are characterized by the trade-off between labor income and leisure. We obtain a closed-form solution to the optimization problem by using the martingale and duality method, and investigate theoretical implications of it. The most interesting finding for the optimal job switching policy is that the borrowing constraints in the financial market can decrease the effective flexibility in labor supply of the agent in the labor market. Thus, an environment of the financial market can affect an agent’s decision making in the labor market. We also show how the effects of the borrowing constraints on the optimal consumption/investment policy reinforce or compete with those of the job switching opportunities.
Keywords: Borrowing constraints; Consumption/investment; Effective flexibility in labor supply; Job choice